Preparation of Phase‐Pure K0.5Na0.5NbO3 Fine Powders by a Solid‐State Reaction at 625°C from a Precursor Comprising Nb2O5 and K, Na Acetates. Issue 2 (19th December 2013) - Senna, Mamoru; Pavlic, Jernej; Rojac, Tadej; Malic, Barbara; Kosec, Maria; Brennecka, G.
<x xml:space="preserve">Abstract</x> Phase‐pure K0.5Na0.5NbO3 (KNN) fine powders were synthesized via a solid‐state route from a homogeneous solid mixture. A colloidal dispersion comprising a mixed ethanol solution of potassium and sodium acetates and Nb2O5 fine particles was attrition milled and dried carefully to avoid water absorption. Two‐step calcination in air at 450°C and 625°C, each for 3 h, resulted in the phase‐pure KNN powders. The volume‐based median diameter of the final product was ca. 0.8 μm. Starting from the same precursors without dissolving the acetates, the phase‐pure KNN was never achieved even when the two calcination temperatures were increased to 550°C and 700°C, in spite of the same milling conditions. Key issues of eliminating second phases were (i) starting from a wet‐milled mixture with a single solution containing both of the A‐site species, and (ii) repeated wet milling of the reaction mixture to disintegrate reaction‐induced agglomerates. These enabled rapid nuclei growth from chemically interacted precursor prior to calcination, and short diffusion path due to repeated deagglomeration, excluding formation of off‐stoichiometric second phases. All these items were confirmed by different analytical tools, among others, thermo‐gravimetry and differential thermal analysis (TG‐DTA), particle size analyses, and XPS at various reaction stages. On the heating stage microscope, a shrinkage onset was observed at 850°C, that is, 150 K lower than that of conventionally prepared KNN, that is, via a solid‐state synthesis from carbonates by a two‐step calcination at 800°C and 750°C, for 4 h each. No second phase was observed after sintering up to 1100°C.